Evaluation of method of placement, timing, and rate of application for anhydrous ammonia in no-till corn production - Stamper, Joshua D. (Kansas State University, 2009)
Anhydrous ammonia (AA) is one of the most commonly used nitrogen (N) fertilizer sources for corn (Zea mays L.) in the US. Traditional knife applicators are slow, have high power requirements and create substantial soil disturbance. Thus, there is considerable interest in high speed, shallow placement, and low draft AA applicators like the newly introduced JD 2510 series, particularly for no-till production systems. The objective of this project was to compare a prototype high speed, low draft applicator (JD) with a traditional knife type AA applicator (TRAD) for irrigated and dryland corn production in the Kansas River Valley. Field studies were conducted from 2007 through 2009. Six N rates ranging from 0 – 224 kilograms N per hectare, in 45 kilogram increments, were applied at 3 application timings, Fall (FALL), Preplant (PRE), and Sidedress (SD) with both type applicators. Gaseous AA emissions were collected over a seven to nine day period after each application for both the TRAD and JD applicators for all application timings. The impact of applicator, timing and N rate was also measured on plant stand, earleaf N content, total N uptake, nitrogen use efficiency and grain yield. Statistically higher post application losses of ammonia at high N application rates were seen at all application timings with the JD applicator. However, these N losses were not of agronomic significance, and did not affect grain yield in 2007 or 2008. In 2009, there did appear to be a significant difference between applicators in grain yield, however this was primarily due to a significant yield decrease at the JD SD 224 kilograms N per hectare treatment from high application loss and resulting plant tissue damage. A significant response to N application was seen every year. Optimum N rate varied between years. FALL and PRE treatments had significantly higher grain yield than SD applications in 2008. However, in 2009 there was no significant difference in N application timing.
Keywords: Anhydrous ammonia; Application; Depth of placement; Corn; Agriculture, Agronomy (0285)